The Effect of Performance Appraisal and Allowances Performance on Employee Performance Through Work Discipline as an Intervening Variable in the Banten Provincial Public Works and Spatial Planning Office - Lala Nurmala; Muhammad Suparmoko; Budi Ilham Maliki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Performance has a very important role because performance is the final result of the employee's process of completing their tasks. Employees who complete their tasks well and correctly will have high performance. The purpose of this study is to examine the effect of performance appraisal and performance allowances on employee performance through work discipline as an intervening variable. The approach used in this study is a quantitative approach with a descriptive causality design. In this study, data collection used a survey method through the distribution of questionnaires. The population of the study was 204 employees, and the sample was taken using a simple random sampling technique of 67 ASN PUPR employees of Banten Province. The analysis method used in this study used the SEM (Structural Equation Modeling) method and testing was carried out with the Partial Least Square (PLS) program using the assistance of SmartPLS v.3.2.9 software.The results of the study indicate that H1: there is a positive and significant influence of performance appraisal on employee performance, H2: there is a positive and significant influence of performance allowances on employee performance, H3: there is a positive and significant influence of performance appraisal on work discipline, H4: there is a positive and significant influence of performance allowances on work discipline, H5: there is a positive and significant influence of work discipline on employee performance, H6: there is a positive and significant influence of performance appraisal on employee performance through work discipline, H7: there is a positive and significant influence of performance allowances on employee performance through work discipline.